Sermon of Lady Zahra (Peace Be Upon Her) Stylistic Study - Najm, Mr. Eman Saadoun (Journal of Research in Innovative Teaching and Inclusive Learning, 2024)
Praise be to Allah, Lord of the Worlds, and prayers and peace be upon the best of His Messengers and the Seal of His Prophets, Muhammad and his pure and immaculate family. Eloquence is an art of speech, and is distinguished by its multiple sciences, and only those with a broad culture in science can master it. Lady Fatima al-Zahra (peace be upon her) is one of the women known for her eloquence in the arts of speech. How could she not be, when she is the daughter of the Messenger of Allah (peace be upon him), and the wife of the gate of knowledge, Ali (peace be upon him). She was raised with a scientific, cultural, and Islamic upbringing, in which all sciences were instilled in her since her childhood. This culture, including eloquence, appeared in her style in addressing others, which was distinguished by the inclusion of multiple arts of eloquence and speech. To clarify this eloquence, we chose our research entitled (The Sermon of Lady Zahra (peace be upon her) a stylistic study), to stand on the most important arts of eloquence of speech in Lady Zahra (peace be upon her), and therefore the research came with an introduction in which I clarified the concept of the sermon, then I divided the research into three sections: In the first section, I studied the artistic structure of the sermon and the linguistic structures, in the second section I studied the rhetorical images, and in the third section I studied the musical structure, and I concluded the research with aconclusion in which I clarified the most important results of the research.